2012
DOI: 10.1128/cvi.05633-11
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the QuantiFERON-Cytomegalovirus (CMV) Assay for Detection and Estimation of the Magnitude and Functionality of the CMV-Specific Gamma Interferon-Producing CD8+T-Cell Response in Allogeneic Stem Cell Transplant Recipients

Abstract: The performance of the QuantiFERON-cytomegalovirus (CMV) assay was compared to that of a flow cytometry intracellular cytokine staining (ICS) method for the detection of CMV-specific gamma interferon (IFN-␥)-producing CD8؉ T-cell responses in allogeneic stem cell transplant (allo-SCT) recipients and for estimations of their magnitude and functionality. A total of 90 whole-blood specimens from 23 allo-SCT recipients was analyzed by both methods. Overall, the percentage of specimens that yielded concordant resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…Fourth, we found that the PPV and NPV of the detection of total IFN‐γ‐producing CD8 + T cells (and also total TNF‐α‐producing CD8 + T cells) for the occurrence of CMV DNAemia were comparable to those of the detection of polyfunctional CD8 + T cells (either CD107a + or CD107a − ). This was previously shown by our group for IFN‐γ‐producing CD8 + T measured by the QuantiFERON CMV assay .…”
Section: Discussionsupporting
confidence: 76%
“…Fourth, we found that the PPV and NPV of the detection of total IFN‐γ‐producing CD8 + T cells (and also total TNF‐α‐producing CD8 + T cells) for the occurrence of CMV DNAemia were comparable to those of the detection of polyfunctional CD8 + T cells (either CD107a + or CD107a − ). This was previously shown by our group for IFN‐γ‐producing CD8 + T measured by the QuantiFERON CMV assay .…”
Section: Discussionsupporting
confidence: 76%
“…This assay is analogous to the QuantiFERON-TB assay that has been widely adopted for tuberculosis. Although QantiFERON-CMV is less sensitive than flow cytometry assays, 96 it is simple and reproducible and has been validated in HSCT recipients with similar results to other immune monitoring assays. 97 There are no studies that yet conclusively demonstrate the safety of ceasing CMV monitoring based solely on the demonstration of CMV immunity.…”
Section: Measurement Of CMV Specific Immune Function In the Clinicmentioning
confidence: 96%
“…In comparison to ICS, QT is as specific but less sensitive [68]. However, ICS is definitely more difficult to standardize and not suitable for automation.…”
Section: Diagnostic Methods Based On T Cell Reactivitymentioning
confidence: 99%